Comprehensive Environmental Mass Spectrometry. - Lebedev, Albert T. (Advanced topics in environmental science., 2012)
Mass spectrometry is the most sensitive, rapid and informative analytical tool available. In full colour throughout, this book describes the power of this technique in resolving environmental issues, demonstrating how real-world complex problems can be solved in a simple and elegant way. The book begins with the general principles of mass spectrometry, then proceeds to describe a range of techniques including imaging, ambient mass spectrometry, miniaturisation and isotope ratio mass spectrometry. A variety of applications are covered, including different types of environmental pollutants, such.